(untitled) (Modern education and development, 2025)
This article presents a comparative analysis of online and traditional forms of education, focusing on pedagogical effectiveness, psychological impact, student motivation, and academic outcomes. The results of the research reveal that both educational models possess distinct advantages and limitations. Online education promotes self-directed learning and flexibility, whereas traditional education enhances social interaction and direct teacher engagement. Blended learning is introduced as a dynamic alternative capable of responding to the needs of modern education. Drawing on leading scholarly theories and recent empirical studies, the article elaborates on the strengths, challenges, and potential for improvement in both modalities.